Hubungan Nyeri Dismenorea Dengan Tingkat Aktivitas Belajar Siswi di SMP Negeri 1 Depok, Sleman, Yogyakarta - Vinakurnia Lestari; Nurul Mahmudah (Yayasan Literasi Sains Indonesia, 2026)
Learning activity is the physical and mental involvement of female students in the learning process, which plays a crucial role in learning success and academic achievement. Learning activity can be influenced by physical health conditions. One of which is dysmenorrhea pain, which is often experienced by female adolescent during menstruation. Dysmenorrhea pain can cause discomfort and reduce concentration, motivation, and participation in school learning activities. The study aims to determine the correlation between dysmenorrhea pain and students' learning activity levels at SMPN (State Junior High School) 1 Depok, Sleman, Special Province of Yogyakarta in 2025. This study employed quantitative methods with an observational analytical design and a cross- sectional approach. The study population was all 83 eighth-grade female students who had menstruated and experienced dysmenorrhea, with a sample of 68 students selected using a purposive sampling technique. Dysmenorrhea pain was measured using the Numeric Rating Scale (NRS), while learning activity was measured using a questionnaire. Data analysis was performed using the Spearman Rank test. The results showed that the majority of respondents experienced mild dysmenorrhea pain (37 students, similar to 54.41%), and learning activity was severely disrupted (39 students, similar to 57.35%). The Spearman Rank test showed a p-value of 0.028 (p<0.05). Thus, it concludes that there is a relationship between dysmenorrhea pain and students' learning activity levels.